A MOLINA AND ALBIR-BASED ANALYSIS OF CLARITIN® MEDICAL LEAFLET TRANSLATION - Yeni Pujihastuti; Evert Haryanto Hilman (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
This study aims to examine the translation techniques applied in the Indonesian version of the Claritin® medical brochure and to identify the frequency distribution of each technique in conveying medical information. The urgency of this study lies in the critical need for accurate and comprehensible translation of medical information to ensure public safety and effective health communication. The study also offers novelty by focusing specifically on pharmaceutical brochure translation within the framework of Molina and Albir’s (2002) translation techniques, which remain underexplored in this type of text. A qualitative descriptive research design was employed. The data were collected using purposive sampling from selected segments of the Claritin® medical brochure that contain relevant translation features. The data analysis was conducted based on Molina and Albir’s (2002) translation techniques framework, focusing on literal translation, amplification, transposition, reduction, and borrowing. The findings reveal that literal translation is the most frequently used technique, accounting for 44% (22 instances) of the data. It is followed by borrowing (20%, 10 instances), transposition (16%, 8 instances), amplification (12%, 6 instances), and reduction (8%, 4 instances). These results indicate that literal translation plays a dominant role in maintaining the accuracy and consistency of medical terminology. In conclusion, the study highlights that the selection of appropriate translation techniques is essential to ensure that medical information is not only accurate and reliable but also accessible and understandable for the general public. The study contributes to translation studies, particularly in the field of medical and pharmaceutical translation, by providing empirical evidence on the practical application of translation techniques in real-world health communication materials.